2014
DOI: 10.1139/cjfas-2013-0217
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale migration patterns of silver American eels from the St. Lawrence River to the Gulf of St. Lawrence using acoustic telemetry

Abstract: Downstream migration of silver American eels (Anguilla rostrata) from the St. Lawrence system was examined using acoustic telemetry. One hundred and thirty six silver American eels were tagged, and their passage was recorded using fixed acoustic arrays covering a 420 km distance along the St. Lawrence River and Estuary. Eighty-nine percent of the tagged eels were detected. All migrant eels (111) exhibited unidirectional and downstream movements, but the migration was not completed in one continuous direct move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…A possible interpretation of migration patterns shown here, which has been raised by other studies, is that sea migration could be a two‐step migration process (Durif et al , ; Aarestrup et al , ; Béguer‐Pon et al , ; Stein et al , ). It has been reported that A .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A possible interpretation of migration patterns shown here, which has been raised by other studies, is that sea migration could be a two‐step migration process (Durif et al , ; Aarestrup et al , ; Béguer‐Pon et al , ; Stein et al , ). It has been reported that A .…”
Section: Discussionsupporting
confidence: 92%
“…anguilla may exploit outgoing tidal currents while migrating in the transitional and sea‐lough compartments with 92% of migration initiations occurring at these times. This accords with findings by Béguer‐Pon et al () who reported that American silver eels Anguilla rostrata (LeSeuer 1817) use nocturnal ebb‐tide transport to migrate out of the St Lawrence Estuary. The A .…”
Section: Discussionmentioning
confidence: 99%
“…Such speeds and those described above for eels within Lake Manapouri, are within the range of those recorded for female silver eels of other species e.g . Anguilla anguilla L.: 1.08–4.32 km/hr (Behrmann‐Godel & Eckmann, ); 2.02 km/hr, (Bultel et al., ); Anguilla rostrata LeSueur: 0.83 km/hr (Béguer‐Pon et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Ancestors of anguillid eels were tropical marine species (Tsukamoto & Aoyama, ), and hence anguillids have retained tropical marine spawning, necessitating extensive migrations for temperate species. Prior to their seaward migration, silver eels are often subject to many anthropogenic impacts in freshwater environments, and these can negatively impact both the quantity (Dekker, ) and quality (Béguer‐Pon et al., ) of silver eels escaping to sea. Hydroelectric dams, in particular, can cause delays to downstream migrations and high mortality of eels that enter station intakes (Richkus & Dixon, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation